Implementasi Perjanjian Perdagangan Indonesia–Jepang Economic Partnership Agreement (IJEPA) dalam Mendukung Ekspor Indonesia ke Jepang - Gabriella Dofani Natalia; Muhammad Prakoso Aji; Reza Pahlevi Chairul (FISIP UPNVJ, 2026)
Abstract This article aims to analyze the implementation of the Indonesia-Japan Economic Partnership Agreement (IJEPA) in supporting Indonesian exports to Japan, focusing on the role of the Directorate of Export and Import Facilitation, Ministry of Trade of the Republic of Indonesia, particularly in the issuance of Certificates of Origin (COO) Form IJEPA. This study uses a qualitative descriptive approach with data collection methods including observation, interviews, and documentation. The theories used in this research are Public Policy Implementation Theory and Communication Concepts.The results show that institutionally, the implementation of IJEPA has been carried out in accordance with the existing regulatory framework, primarily through the provision of preferential tariff facilities and strengthening the Electronic Certificate of Origin (e-COO) system. However, the effectiveness of utilizing these facilities is still limited by procedural complexity, limited technical understanding among exporters, and uneven institutional capacity among issuing authorities. Therefore, optimizing the implementation of IJEPA requires strengthening institutional capacity, improving service quality, and simplifying administrative procedures to increase the utilization of preferential tariff facilities more widely and sustainably. Keywords: IJEPA, Indonesian Exports, Certificate of Origin, Policy Implementation